Biofuels, Land Grabbing and Food Security in Africa - Havnevik, Kjell; Matondi, Prosper B.; Beyene, Atakilte (Africa Now, 2011)
Energy crisis and climate change have generated global demands for alternative non-fossil fuel sources. This has led to a rapid increase of investments in production of liquid biofuels based on agricultural feed stocks such as sugar cane. Most African governments see biofuels as a potential for increasing agricultural productivity and export incomes and thus strengthening their national economies, improving energy balances and rural employment. At the same time climate change may be addressed through reduction of green house gas emissions. There are, however, a number of uncertainties mounting that challenge this scenario. Using in-depth African case studies this book addresses this knowledge gap by examining the impacts of large-scale biofuel production on African agriculture in regard to vital land outsourcing and food security issues. The surge for African biofuels has also opened space for private investors both domestic and external to multiply and network 'independently' of the state. The biofuel expansion thus generates new economic alliances and production relations, resulting in new forms of inclusions and exclusions within the rural population. An essential book for anyone wishing to understand the startling impact of biofuels and land outsourcing on Africa.